2013
DOI: 10.1038/nature12143
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic programming of systemic ageing involving IKK-β, NF-κB and GnRH

Abstract: SummaryAging is a result of gradual and overall functional deteriorations across the body; however, it is unknown if an individual tissue works to primarily mediate aging progress and lifespan control. Here we found that the hypothalamus is important for the development of whole-body aging in mice, and the underlying basis involves hypothalamic immunity mediated by IKKβ/NF-κB and related microglia-neuron immune crosstalk. Several interventional models were developed showing that aging retardation and lifespan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
700
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 766 publications
(731 citation statements)
references
References 44 publications
21
700
0
10
Order By: Relevance
“…Immunofluorescent staining for GFAP was less intense in the ARH of 18‐month‐old Ames male mice (Fig. 3) compared to littermate control mice ( P  < 0.05), consistent with other work associating long lifespan with lower hypothalamic inflammation (Zhang et al ., 2013). Thus, Ames dwarf mice resemble CL mice in that both mice have lower levels of hypothalamic inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunofluorescent staining for GFAP was less intense in the ARH of 18‐month‐old Ames male mice (Fig. 3) compared to littermate control mice ( P  < 0.05), consistent with other work associating long lifespan with lower hypothalamic inflammation (Zhang et al ., 2013). Thus, Ames dwarf mice resemble CL mice in that both mice have lower levels of hypothalamic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has suggested that hypothalamic inflammatory pathways may influence mouse lifespan in either direction (Zhang et al ., 2013). Activation of NF‐kB dependent cytokine production and glial activity increases with age in the hypothalamus, and augmentation of this effect, either genetically or by viral‐mediated gene delivery, can shorten mouse lifespan (Zhang et al ., 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…DNA damage response and its downstream GATA4, p38MAPK, and mTOR pathways regulate SASP (Rodier et al ., 2009; Freund et al ., 2011; Kang et al ., 2015; Laberge et al ., 2015). All of these pathways converge on NF‐ĸB, the master transcription regulator that controls the expression of immune‐responsive genes (Zhang et al ., 2013; Guo et al ., 2014). A recent study showed SASP gene expression required cGMP‐AMP (cGAMP) synthase (cGAS) in mouse and human senescence model in vitro induced by DNA damage and ionizing radiation (Yang et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%